Afferent Pathway-Mediated Effect of α1 Adrenergic Antagonist, Tamsulosin, on the Neurogenic Bladder After Spianl Cord Injury - Han, Jin-Hee; Kim, Sung-Eun; Ko, Il-Gyu; Kim, Jayoung; Kim, Khae Hawn (International neurourology journal, 2017)
Purpose: The functions of the lower urinary tract (LUT), such as voiding and storing urine, are dependent on complex central neural networks located in the brain, spinal cord, and peripheral ganglia. Thus, the functions of the LUT are susceptible to various neurologic disorders including spinal cord injury (SCI). SCI at the cervical or thoracic levels disrupts voluntary control of voiding and the normal reflex pathways coordinating bladder and sphincter functions. In this context, it is noteworthy that α1-adrenoceptor blockers have been reported to relieve voiding symptoms and storage symptoms in elderly men with benign prostatic hyperplasia (BPH). Tamsulosin, an α1-adrenoceptor blocker, is also considered the most effective regimen for patients with LUT symptoms such as BPH and overactive bladder (OAB). Methods: In the present study, the effects of tamsulosin on the expression of c-Fos, nerve growth factor (NGF), and nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-d) in the afferent micturition areas, including the pontine micturition center (PMC), the ventrolateral periaqueductal gray matter (vlPAG), and the spinal cord (L5), of rats with an SCI were investigated. Results: SCI was found to remarkably upregulate the expression of c-Fos, NGF, and NADPH-d in the afferent pathway of micturition, the dorsal horn of L5, the vlPAG, and the PMC, resulting in the symptoms of OAB. In contrast, tamsulosin treatment significantly suppressed these neural activities and the production of nitric oxide in the afferent pathways of micturition, and consequently, attenuated the symptoms of OAB. Conclusions: Based on these results, tamsulosin, an α1-adrenoceptor antagonist, could be used to attenuate bladder dysfunction following SCI. However, further studies are needed to elucidate the exact mechanism and effects of tamsulosin on the afferent pathways of micturition. KCI Citation Count: 8